Efficacy and safety of high-dose Xueshuantong injection (lyophilised) in reducing the incidence of major adverse cardiovascular events in patients with unstable angina: a protocol of a randomised, parallel-arm, controlled, double-blind and multicentre clinical trial based on dual antiplatelet therapy. Issue 8 (26th August 2020) - Long, Wenjie; Liao, Huili; Huang, Xi; Liu, Qingqing; Tang, Yaqing; Lu, Liming; Liu, Jianhong; Yuan, Tianhui; Ling, Yan; Hong, Yu; Duan, Jiao; Lin, Weiji; et al.
Abstract : Introduction: Unstable angina (UA), referred to as acute coronary syndrome (ACS), causes unexpected chest pain. Xueshuantong injection (lyophilised) (XST) is a traditional Chinese herbal injection having the potential to treat ACS. However, no clinical trial has been performed in this field. This clinical trial aims to examine the efficacy and safety of XST. Methods and analysis: This is a randomised, parallel-arm, controlled, double-blind and multicentre clinical trial. A total of 1200 participants with UA will be enrolled in a 1:1 ratio, with 600 patients included in the XST treatment group and 600 with 1/20th dose in the control group. The efficacy assessment and major adverse cardiovascular events will be observed, and the frequency of angina attack, angina pectoris will be examined at the start and end of the run-in period. All adverse events will be recorded, regardless of the severity, to assess the safety of XST. The baseline characteristics of patients will be summarised and compared using the t test or non-parametric statistical test. Qualitative data will be analysed using the χ 2 or Fisher exact tests, Cochran–Mantel–Hasenszel test and Wilcoxon test. Ethics and dissemination: This trial has been approved by the Research Ethics Committee of The First Affiliated Hospital of Guangzhou University of Chinese Medicine, China (approval number: ZYYEC [2017] 0021). Written informed consent will be obtained from all participants. The results of this trial will be disseminated to the public through academic conferences and peer-reviewed journals. Trial registration: This study was registered on the Chinese Clinical Trial Registry (http://www.chictr.org.cn/ ) with the ID ChiCTR1800015911.